(untitled) - Chalk, B. S. (New York, 2004)
Computer Organisation and Architecture provides a concise, gently paced, introduction to how computers work, and explains how the various hardware components are organised and interconnected to provide a platform upon which programs can be executed. It takes a step-by-step approach suitable for first-year undergraduates coming to the subject for the first time, and provides complete coverage for one-semester courses in this area
Keywords: Business,Electronic data processing personnel,Electronic data processing departments; Data processing,Management